Circulating Soluble CD163: A Potential Predictor for the Functional Outcome of Acute Ischemic Stroke - Sun, Houchao; Zhang, Xiaogang; Ma, Jingxi; Liu, Zhao; Qi, Yunwen; Fang, Li; Zheng, Yongling; Cai, Zhiyou (Frontiers in Neurology, 2021)
Background CD163 is a scavenger receptor present on innate immune cell populations which can be shed from cellular membranes with the cleavage by the metalloprotease ADAM17, generating a soluble peptide with lympho-inhibitory properties. This study aimed to investigate the circulating levels and pathological relevance of soluble CD163 (sCD163) in acute ischemic stroke (AIS). Methods This study recruited 300 AIS patients and 78 healthy controls, and patients were followed-up for one month for observation of functional outcomes. Neurological functions of patients were assessed by NIH Stroke Scale (NIHSS) and the modified Rankin Scale (mRS). Plasma concentrations of sCD163 at baseline were determined by Elisa. Results We found that AIS patients had significantly higher plasma sCD163 concentrations than control. Patients with high sCD163 concentrations had significantly a higher speed of functional improvement. Plasma sCD163 concentrations were positively associated with NIHSS scores and infarction volume at baseline. Plasma sCD163 were positively associated with the functional improvement and negatively associated with the risk of poor functional outcome during follow-up. Conclusions These findings indicate that circulating sCD163 is a potential biomarker which is associated with disease severity and functional outcome of AIS patients.